Funding societies: Using fintech to support small businesses in Singapore - LEE, Michelle P. (Institutional Knowledge at Singapore Management University, 2020)
Jacquelyn Yang is the Senior Marketing Manager at a young Singapore company, Funding Societies, in the nascent debt crowdfunding scene in the island city-state. Debt crowdfunding, also referred to as peer-to-peer (P2P) lending, represents an alternative source of loans for businesses to borrow money. P2P companies are different from banks in that they operate through online platforms, utilise data analytics and algorithms for credit risk assessment, and have much shorter turnaround times for loan approvals than the banks. Moreover, while banks lend money to companies using customer deposits, P2P companies play the part of a matchmaker by enabling individual investors to put money directly towards funding a particular loan. Crowdfunding is part of a growing worldwide trend in FinTech innovations. It is perhaps unsurprising then that there were no fewer than seven P2P lenders in a mere three years since the first company, MoolahSense, was founded in Singapore in 2013. The rivalry is intense and exacerbated by the fact that business loans tend to be a product that does not differentiate on non-price factors. In addition, all of the competing companies, with the exception of CoAssets, appear to be competing head-on for the same general SME market. To improve the effectiveness of their marketing efforts, it would be helpful for Funding Societies to move away from a ‘shotgun’ approach to marketing to more carefully identify the segments or types of SMEs that would be more inclined to borrow from the crowdfunding market. These SMEs would represent the ‘lower hanging fruit’ so-to-speak, and identifying who they are will help Funding Societies better focus their marketing resources. Understanding the factors that influence an SME’s decision to borrow from a P2P lender will help Funding Societies build a strong competitive advantage, giving it an edge over its P2P competitors as well as banks. What should Yang focus the marketing strategy on? This case exposes students to a burgeoning area within FinTech and gives them an understanding of how P2P lending works. Students will learn to apply the principles of market segmentation and targeting for an innovative service. The case also teaches students to think critically about who the competition is and who the target market should be, and leverage that understanding to build a competitive advantage by considering what the target market values and how to deliver it better.